Optimizing InGaN/GaN MQW Blue LED Performance: Integrating Simulation and Growth Approaches - K. Meel; P. Mahala; S. Singh (Current Perspective to Physical Science Research Vol. 8, 2024)
This paper presents the optimization of the multi-quantum well-based Light Emitting Diode (LED) structure. Technology has been developed for LEDs of red, violet, green, blue etc but for Solid-State lighting, it is also important to concentrate on white lights due to their high-energy efficiency and reliable lifetime. We investigate the electrical and optical properties of the device on several factors like well width, barrier width, and the number of quantum wells and then optimize the structure. The structure has been considered to have epitaxial layers of Gallium Nitride and Indium Gallium Nitride material to be grown using Metal Organic Chemical Vapour Deposition on a C-plane Sapphire substrate of thickness 300 nm. The device is optimized for a well width and barrier width of 3nm and 6nm respectively, consisting of five quantum wells. Simulations were carried out using the Silvaco ATLAS TCAD simulation program (Silvaco International, USA). The optimized Multiple Quantum Well LED structures were indigenously grown by the MOCVD system on a c-plane (0001) sapphire substrate. Blue LEDs at the chip level were fabricated. I-V characteristics were measured for the fabricated chips. Fabricated blue LED has a peak emission wavelength of 453 nm which is in the blue region.